2017
DOI: 10.2174/1389203717666160724192305
|View full text |Cite
|
Sign up to set email alerts
|

Plant Proteomics and Peptidomics in Host-Pathogen Interactions: The Weapons Used by Each Side

Abstract: Environmental biotic stress factors act continuously on plants, through multiple molecular interactions that eventually lead to the establishment and progress of symbiotic or pathogenic complex interactions. Proteins and peptides play noteworthy roles in such biological processes, usually being the main effectors since the initial recognizing and elicitor functions until the following transduction, gene regulation and physiological responses activities. Ranging from specific regulators to direct antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Plants are constantly exposed to a large variety of pathogenic microorganisms, and they produce natural compounds as resistance factors, such as constitutive peptides and proteins. [54][55][56] Peptides are a very common chemical component of Capsicum seeds. 50,57 In this context, some studies have suggested that plant-derived peptide fractions exhibit antiadhesive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are constantly exposed to a large variety of pathogenic microorganisms, and they produce natural compounds as resistance factors, such as constitutive peptides and proteins. [54][55][56] Peptides are a very common chemical component of Capsicum seeds. 50,57 In this context, some studies have suggested that plant-derived peptide fractions exhibit antiadhesive properties.…”
Section: Discussionmentioning
confidence: 99%
“…Possibilities to overcome existing difficulties and potentialities are also addressed. Such as for genomics, transcriptomics and epigenomics, a review of aspects of proteomics and peptidomics studies related to plant defense is covered in a specific article (Silva et al [14]), confirming the existence of an abundant molecular richness as a result of post-transcriptional modifications, emphasizing the complexity of the plant biological system.…”
mentioning
confidence: 99%